A new perspective on controllability properties for dynamical systems - Rocha, Paula; Wood, Jeffrey (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we study the properties of weak and strong controllability as newly defined in (Rocha, 1995) for delay-differential systems in a behavioural setting, now for the multidimensional case. Further, we give an overview of the relationships between these properties and the original behavioural controllability concept introduced in (Willems, 1988).
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka